The Effect of Working Capital Turnover on Profitability at Telkom Indonesia Tbk - Fitrianingsih, Fitrianingsih; Alwi, Alwi; Huda, Nurul (Journal of Economics, Management and Accounting (JEMA), 2024)
This study aims to produce information in the form of a more in-depth explanation of the effect of working capital turnover on return on equity. And obtained the results from processed data on how much the working capital turnover affects return on equity (ROE). The research method used in this study is associative which is to know the influence between two or more variables in the form of annual financial statements from 2018 to 2022. Based on the calculation with the simple linear regression equation Y = 27.890 + 0.080X, it means that if the working capital turnover value is 0, the return on equity (ROE) value is 0.080% and if the working capital turnover increases by Rp. 1,- then the return on equity will increase by 0.080%. The value of R = 0.725 implies that the relationship between working capital turnover and return on equity (ROE) is strong. While the value of R2 = 0.525 or 52.5%, meaning that the return on equity is influenced by the turnover of working capital of 52.5%, the remaining 47.5% is influenced by other variables that are not studied. Meanwhile, from the T test resulting in a sig of 0.018 < 0.05, the H1 will be accepted, and based on the Thitung test of 2.975 which means that the variable of the T value of the calculation is greater than the Table of 1.860 proves that the turnover of working capital has a significant effect on return on equity (ROE).